Bioproduction of High-Concentration 4-Vinylguaiacol Using Whole-Cell Catalysis Harboring an Organic Solvent-Tolerant Phenolic Acid Decarboxylase From Bacillus atrophaeus - Li, Lulu; Long, Liangkun; Ding, Shaojun (Frontiers in Microbiology, 2019)
The compound 4-vinyl guaiacol (4-VG) is highly valued and widely applied in the pharmaceutical, cosmetic, and food industries. The bioproduction of 4-VG from ferulic acid (FA) by nonoxidative decarboxylation using phenolic acid decarboxylases is promising but has been hampered by low conversion yields and final product concentrations due to the toxicities of 4-VG and FA. In the current study, a new phenolic acid decarboxylase (BaPAD) was characterized from Bacillus atrophaeus. The BaPAD possessed excellent catalytic activity and stability in various organic solvents. Whole Escherichia coli cells harboring intracellular BaPAD exhibited greater tolerances to FA and 4-VG than those of free BaPAD. A highly efficient aqueous-organic biphasic system was established using 1-octanol as the optimal organic phase for whole-cell catalysis. In this system, a very high concentration (1580 mM, 237.3 g/L) of 4-VG was achieved in a 2 L working volume bioreactor, and the molar conversion yield and productivity reached 98.9% and 18.3 g/L/h in 13 h, respectively.